Extended hamming distance method for measuring the perfomance of academic staff - Rasyida Md Saad (Institute of Engineering Mathematics, 2015)
A case study involving the staff performance evaluation is done to validate the extended Hamming distance method. The data are taken from the Institute of Engineering Mathe matics (IMK) in Universiti Malaysia Perlis (UniMAP). The performance appraisal reports which are based on Annual Performance Target (SKT) from that institute are used in order to clarify this method. This research is also solely focusing on the performance appraisal of the academic staff at IMK. By using the proposed method, the ranking of academic staff performance will be made, hence will help the management in IMK to identify the academic staff that performs well in term of their works.